The design and implementation of a fourth generation programming language - Iverson, Carn Martin (Rhodes University, Faculty of Science, Department of Computer Science, 1989)
IV is a very high level language designed for use in a real time production control environment. While most fourth generation languages are intended for use by end users, IV is more suitable for skilled professional programmers. One of the major design objectives of IV is a dramatic improvement in programmer efficiency during application program development. Non-procedural constructs provided by the language and the use of a number of interactive development tools provide an environment for achieving this goal. This report presents a language proposal for IV, and addresses related design and implementation issues.
Keywords: Programming languages (Electronic computers); Fourth generation computers